A Case for Inter-State Cooperation in India for Excellence in in Sports. - Mohan, Jitendra (2008)
Sports emerge out of a drive for potential, courage, and great human diligence. Aggressive competition is an expression of human desire to excel and to be the best. The road to peak performance is, however, based on long term preparation, planning and execution, both at the level of the athlete as well as the parents, coach, experts, administrators and the scientists. Any excellence in sports is an outcome of collaborative inputs by the society which believes in sports culture as an expression of civilization, human excellence and resource utilization. The paper discusses various reasons behind the underdeveloped performance of India in various sports ever since the Olympics in 1896 and its standing among other European and Asian countries. A methodological analysis of the wasteful and avoidable expenditure in India, under-utilization of resources and facilities, and over-expenditure on fruitless activities brings forth a variety of issues related to an unhealthy competition as opposed to the desirability of welding cooperation and competition.